Malassezia pachydermatis from brown bear: A comprehensive analysis reveals novel genotypes and distribution of all detected variants in domestic and wild animals - Hađina, Suzana; Bruvo Mađarić, Branka; Kazazić, Snježana; Paradžik, Tina; Reljić, Slaven; Pinter, Ljiljana; Huber, Đuro; Vujaklija, Dušica (Frontiers in Microbiology, 2023)
Malassezia pachydermatis (phylum Basidiomycota, class Malasseziomycetes) is a zoophilic opportunistic pathogen with recognized potential for invasive infections in humans. Although this pathogenic yeast is widespread in nature, it has been primarily studied in domestic animals, so available data on its genotypes in the wild are limited. In this study, 80 yeast isolates recovered from 42 brown bears (Ursus arctos) were identified as M. pachydermatis by a culture-based approach. MALDI-TOF mass spectrometry (MS) was used to endorse conventional identification. The majority of samples exhibited a high score fluctuation, with 42.5 % of isolates generating the best scores in the range confident only for genus identification. However, the use of young biomass significantly improved the identification of M. pachydermatis at the species confidence level (98.8 %). Importantly, the same MALDI-TOF MS efficiency would be achieved regardless of colony age if the cut-off value was lowered to ≥ 1.7. Genotyping of LSU, ITS1, CHS2, and β-tubulin markers identified four distinct genotypes in M. pachydermatis isolates. The most prevalent among them was the genotype previously found in dogs, indicating its transmission potential and adaptation to distantly related hosts. The other three genotypes are described for the first time in this study. However, only one of the genotypes consisted of all four loci with bear-specific sequences, indicating the formation of a strain specifically adapted to brown bears. Finally, we evaluated the specificity of the spectral profiles of the detected genotypes. MALDI-TOF MS exhibited great potential to detect subtle differences between all M. pachydermatis isolates and revealed distinct spectral profiles of bear-specific genotypes.